Renewed evidence of environmental sustainability from globalization and energy consumption over economic growth in China - Bekun, Festus Victor; Yalciner, Kursat; Etokakpan, Mfonobong Udom; Alola, Andrew Adewale (Springer Heidelberg, 2020)
This study is primarily motivated by exploring the role of globalization, energy intensity over economic expansion, and its impact on environmental sustainability in China. To this end, a sequence of econometrics tests were conducted to address this hypothesized relationship. The choice of China is informed by intense industrial activities and being one of the leading world economies. Annual frequency data from 1971 to 2015 is utilized for the current study. Empirical finding from novel and robust Bayer and Hanck combined cointegration test supports cointegration equilibrium relationship among the variables under review. This indicates a convergence between the explanatory variable and the explained variable in the fitted model. Further empirical evidence shows a positive statistically significant relationship between real income, ecological footprint, and globalization index. This outcome is insightful for environmental economists and policymakers. The causality analysis supports the growth-induced energy consumption hypothesis. Based on these revelations, policy direction for the energy sector in China in the face of global interconnectedness is offered in the concluding remark of this study.
Keywords: Energy intensity; Globalization; Energy conservation; Pollutant emission; China